Human Poisoning from Poisonous Higher Fungi: Focus on Analytical Toxicology and Case Reports in Forensic Toxicology - Estelle Flament; Jérôme Guitton; Jean-Michel Gaulier; Yvan Gaillard (MDPI AG, 2020)
Several families of higher fungi contain mycotoxins that cause serious or even fatal poisoning when consumed by humans. The aim of this review is to inventory, from an analytical point of view, poisoning cases linked with certain significantly toxic mycotoxins: orellanine, α- and β-amanitin, muscarine, ibotenic acid and muscimol, and gyromitrin. Clinicians are calling for the cases to be documented by toxicological analysis. This document is therefore a review of poisoning cases involving these mycotoxins reported in the literature and carries out an inventory of the analytical techniques available for their identification and quantification. It seems indeed that these poisonings are only rarely documented by toxicological analysis, due mainly to a lack of analytical methods in biological matrices. There are many reasons for this issue: the numerous varieties of mushroom involved, mycotoxins with different chemical structures, a lack of knowledge about distribution and metabolism. To sum up, we are faced with (i) obstacles to the documentation and interpretation of fatal (or non-fatal) poisoning cases and (ii) a real need for analytical methods of identifying and quantifying these mycotoxins (and their metabolites) in biological matrices.